ANALISIS TENSILE STRENGTH KOMPOSIT SERAT DAUN AGEL BERORIENTASI ARAH 0 DERAJAT DENGAN VARIASI MATRIKS - Pinandhita, Lazuardy Rahendra (Institut Teknologi Dirgantara Adisutjipto, 2022)
Composite is a material that is made by combining two types of materials that have different properties. Composites material made of natural fiber continue to be researched and developed to become an alternative material for metal substitutes. Natural fibers have advantages such as environmentally friendly, low density, recyclable, biodegradable, non-toxic, low cost, and good non-abrasive and heat retaining properties. The test carried out is a tensile test that is adjusted to the ASTM D3039 test standard using a Universal Testing Machine (UTM) tool to obtain stress and strain values. The results of the tensile strength of the agel leaf fiber composite material with an epoxy matrix with fiber direction 00 is 9.588294 MPa and with a polyester matrix in same direction 00 is equal to 7,236818 MPa.